Sistem Peringatan Dini Pemantauan Banjir menggunakan Telegram berbasis Internet of Things - AnathaPindika Wijaya; Rino (Komunitas Dosen Indonesia, 2024)
Technology can be considered a human invention that is used to facilitate human activities. In the current increase and growth of technology, there are many technologies that have been created from time to time. Flooding is a natural disaster that can be caused by human behavior itself. Many floods occur due to blockage of water flow in gutters or drainage systems. The impact of a flood disaster are many things that harm us, if a flood occurs, it doesn't just result in material loss, it can even cause loss of life. Therefore, this research aims to create an Early Warning System for handling flood disasters based on the Internet of Things (IOT) using telegram as a monitoring control. According to the rule, if the water level distance is less than 10 cm, then the water level will be declared safe from flooding. Then, if it is greater than 10 cm and less than 15 cm, a flood warning will be issued, and if the water level is more than 15 cm, there will be a danger of flooding. The results of this research will show that this tool can detect water levels and send a warning/notification from the Telegram application.